PENERAPAN KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TINGKAT SEKOLAH DASAR DI SLBN 1 AMUNTAI TENGAH KABUPATEN HULU SUNGAI UTARA - Ramlan Thalib; Normalasari; Ria Susanti (Prodi PGMI IAI Darul Ulum Kandangan, 2025)
This study aims to determine the strategies, teaching modules, assessment of the merdeka curriculum and what factors influence the implementation of the merdeka curriculum in Islamic religious education at the elementary school level at SLBN 1 Amuntai Tengah, Hulu Sungai Utara Regency. research results: The implementation of the Merdeka Curriculum has been proven to make it easier for Islamic Religious Education teachers to teach students with special needs at SLBN 1 Amuntai. Its flexibility allows for the adjustment of learning materials and methods according to the diverse needs and abilities of students. Assessment emphasizes individual development, not competition between students. The teaching module, which can be accessed via the internet or the Merdeka Teaching platform, provides effective guidance, especially in the early phase of learning (phase A) which focuses on basic material such as the hijaiyah letters, ablution, and the shahada. This curriculum marks a paradigm shift from teacher-centered learning to student-centered learning.